Anaerobic co-digestion of glycerol waste and distillery wastewater for bio-hythane production: Performance and ADM-1 based kinetics - Khaliyah Sani; Sompong O-Thong; Rattana Jariyaboon; Alissara Reungsang; Hidenari Yasui; Prawit Kongjan (Carbon Resources Conversion)
Glycerol waste (GW), with its high carbon content, was co-digested with nitrogen-rich distillery wastewater (DW) in this experiment to evaluate hydrogen and methane production in a two-stage anaerobic digestion (AD) system. Bio-hydrogen potential (BHP) and methane potential (BMP) were conducted under thermophilic conditions (55°C) for the co-digestion of GW and acetone-butanol-ethanol distillery wastewater (ABE-DW) at various mixing ratios of 0:100, 20:80, 40:60, 50:50, 60:40, 80:20, and 100:0 (%VS) to determine the optimal mixing ratio. The highest BHP of 147 mL-H2/g-VS and BMP of 650 mL-CH4/g-VS were achieved at a GW to ABE-DW mixing ratio 50:50. Then. the process proceded with the continuous two-stage anaerobic process which was later implemented with the continuously stirred tank reactor (CSTR) for hydrogen production and the up-flow anaerobic sludge blanket (UASB) reactor for methane production in order to assess system performance. A mixture of GW and DW from commercial ethanol production (ethanol-DW) at a 50:50 mixing ratio was fed into the CSTR at a 4-day HRT, and the CSTR effluent was subsequently fed into the UASB at 21-day and 18-day HRTs. The CSTR achieved a hydrogen yield of 83.6 mL-H2/g-VS, while methane yields in the UASB were 367 mL-CH4/g-VS at a 21-day HRT and 440 mL-CH4/g-VS at an 18-day HRT. Additionally, the original ADM-1 was modified to describe the two-stage anaerobic co-digestion of GW and DW. This enhanced model effectively predicts the performance of the two-stage anaerobic process for co-digesting GW and DW.